Features of Pasture Land Management and Monitoring Using Remote Sensing Materials - KALDYBEKOV, Azamat; BEKTANOV, Bolatbek; RSYMBETOV, Bekzat (Journal of Environmental Management and Tourism; Vol 11 No 5 (2020): JEMT Volume XI Issue 5(45) Fall 2020DO - 10.14505//jemt.v11.5(45).24, 2020)
Land resources play an important role in the development of Kazakhstan’s economy because they are used in the production of agricultural products and have a significant market value. Development and balanced management of agriculture are one of the most important problems of the present time in the context of the agro-industrial policy of Kazakhstan. The article analyzes the usage status of remote sensing technologies for the benefit of the agribusiness and considers and analyzes the application of remote sensing systems using space imaging in solving problems of monitoring pasture lands. The authors highlight the purpose of remote sensing methods for monitoring agricultural land, their potential advantages, and effectiveness, as well as consider the problems and prospects of using satellite data for solving agribusiness problems.